Effect Of Feedinghigh Energy Diet On The Plasma Biochemical Profile And Reproductive Performance Of Lactating Cross Bred Cows (Applied Biological Research, 2017)
A study was conducted for 150 days to assess the effect of high energy  diet on the performance of cross bred cows in early lactation.  Crossbred cows were divided into 3 groups of 6 each. The cows in  2ndand 3rd groups were supplemented daily with 1 and 2 kg energy  supplement (ground maize), respectively. Animal in all groups showed  similar plasma biochemical profile viz., blood urea nitrogen, plasma  calcium, plasma inorganic phosphorus, plasma magnesium, iron and  plasma copper; whereas plasma glucose was high in both maize  supplemented groups. The animals supplemented with 1 kg maize  attained post- partum heat earlier. Though supplementation of ground  maize at 1 and 2kgcow-1 day-1 did not affect plasma biochemical profile  or reproductive performance significantly. Supplementation of ground  maize at 1 kg day-1 cow-1 resulted in higher plasma glucose and reduced  the days to first post-partum service.
Keywords: Conception rate; crossbred cows; early lactation; ground maize; plasma biochemical profile